Edutainment Aquarium Facility Planning with Functionalism Approach in Deli Serdang - Niken Alya Widyasti; Amy Marisa (International Journal of Architecture and Urbanism, 2022)
The ocean is home to many kinds of aquatic species. The state of the sea is currently on the verge of declining because of the waste thrown into it. There has to be a sanctuary to retain the population of the sea animals, such as the aquarium facility. This facility will also inform the public—especially children—about the kinds of species still available today, just like a zoo. With the functionalism architecture approach, the facility is expected to be durable in the long run and more accessible since everything is based on function. This study uses qualitative methods, meaning all the precedents data are from comparative studies, field studies (surveying the site), and theories from books. The result of this study is the implementation of Functionalism Architecture that prioritized usability in the design of edutainment aquarium buildings. Projects with similar functions or methods can use this study as a precedent